2009
DOI: 10.1093/protein/gzp061
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity of microbial transglutaminase as revealed by three-dimensional docking simulation and mutagenesis

Abstract: Transglutaminases (TGases) are used in fields such as food and pharmaceuticals. Unlike other TGases, microbial transglutaminase (MTG) activity is Ca2+-independent, broadening its application. Here, a three-dimensional docking model of MTG binding to a peptide substrate, CBZ-Gln-Gly, was simulated. The data reveal CBZ-Gln-Gly to be stretched along the MTG active site cleft with hydrophobic and/or aromatic residues interacting directly with the substrate. Moreover, an oxyanion binding site for TGase activity may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 42 publications
(48 reference statements)
2
56
0
Order By: Relevance
“…In designing new lipid substrates for MTG, an MTG-reactive Gln-containing peptidyl substrate was conjugated with fatty acids. Previous studies of peptide screening [11] and docking simulations [12] have indicated that N-terminal hydrophobic residues from the reactive Gln residue was critical for substrate recognition by MTG, and we found that MTG recognizes a seven amino acid sequence (GGGSLLQG) at the C terminus of recombinant proteins. [13] With this in mind, we synthesized lipid-modified peptides (C14-1, C16-1, C18-1, Scheme 1 a) in which the N terminus of the MTG-reactive Gln donor peptide was attached to diverse long-chain fatty acids (myristic acid, palmitic acid and stearic acid) using solid-phase peptide synthesis.…”
mentioning
confidence: 57%
“…In designing new lipid substrates for MTG, an MTG-reactive Gln-containing peptidyl substrate was conjugated with fatty acids. Previous studies of peptide screening [11] and docking simulations [12] have indicated that N-terminal hydrophobic residues from the reactive Gln residue was critical for substrate recognition by MTG, and we found that MTG recognizes a seven amino acid sequence (GGGSLLQG) at the C terminus of recombinant proteins. [13] With this in mind, we synthesized lipid-modified peptides (C14-1, C16-1, C18-1, Scheme 1 a) in which the N terminus of the MTG-reactive Gln donor peptide was attached to diverse long-chain fatty acids (myristic acid, palmitic acid and stearic acid) using solid-phase peptide synthesis.…”
mentioning
confidence: 57%
“…Upon examining the crystal structure, we speculated that many of these mutations would react poorly, particularly those located on the internal β‐strands 1 and 4 because they belong to a flat protein surface that does not appear to be complementary to the crevice that forms MTG's active site (Fig. ) . This speculation was invalidated when the most selective and efficient variant was determined to be I6Q, located within β‐strand 1.…”
Section: Resultsmentioning
confidence: 99%
“…There is a shortage of data indicating which residues play a role in binding MTG's glutamine‐containing substrate. Among the most informative works is an alanine scan of 29 active‐site residues, constituting 9% of the apoenzyme's amino acid sequence . A number of residues were found to be critical for activity, crippling MTG when substituted for alanine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessing where to direct the P- 8 to P- 10 ligand residues on to the transglutaminase surface may however be challenging. Computational studies have been performed on the docking of inhibitors to FXIII, TGase2, TGase3, and microbial transglutaminase [47; 48; 49]. Similar to ZED1301, the synthetic inhibitors have not extended all the way to the P- 8 to P- 10 substrate positions.…”
Section: Resultsmentioning
confidence: 99%